2021
DOI: 10.1596/35950
|View full text |Cite
|
Sign up to set email alerts
|

How Did the COVID-19 Crisis Affect Different Types of Workers in the Developing World?

Abstract: We calculate statistics for each individual country using the household weights constructed by the World Bank and national statistics offices. The cross-country averages are calculated as simple averages between the 40 country-level values.The COVID-19 pandemic is the worst global macroeconomic shock since the Great Depression. This brief reports which groups of workers have been hit hardest by the jobs impact following the economic fallout of COVID-19 in developing countries. 1 It complements an earlier stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 0 publications
3
42
0
1
Order By: Relevance
“…Even though our sample only covers data up to 2018, the impact of COVID-19 raises an even gloomier scenario for FLFP in Guatemala. Globally, women suffer larger work stoppage rates than men (Alon et al, 2021;Kugler et al, 2021). Estimates for Guatemala indicate that women were 20 percentage points more likely than men to lose their jobs in the early stages of the pandemic (Cucagna and Romero, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Even though our sample only covers data up to 2018, the impact of COVID-19 raises an even gloomier scenario for FLFP in Guatemala. Globally, women suffer larger work stoppage rates than men (Alon et al, 2021;Kugler et al, 2021). Estimates for Guatemala indicate that women were 20 percentage points more likely than men to lose their jobs in the early stages of the pandemic (Cucagna and Romero, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To combat the pandemic, governments introduced restrictions to socioeconomic activity, and individuals adopted social distancing and modified their behavior in various other ways. As past studies have shown (for example, Bundervoet, Dávalos & Garcia, 2021;Crossley, Fisher & Low, 2021;Egger et al, 2021, Kugler et al, 2021, impacts both across countries and within countries have substantial heterogeneity. In this paper, we investigate the existence of differential impacts of the COVID-19 pandemic on subnational areas based on their fragility, conflict, and violence (FCV) status.…”
Section: Introductionmentioning
confidence: 95%
“…the gendered economic impacts of the COVID-19 pandemic that shows the employment shock from the pandemic disproportionately impacted women (Kugler et al, 2021;Oreffice and Quintana-Domeque, 2021) and women-led firms (Torres et al, 2021;Liu, Wei and Xu, 2021).…”
Section: Introductionmentioning
confidence: 99%